Screening of Actinomycetes from Soil for Antibacterial Activity - Budhathoki, Shailesh; Shrestha, Anima (Nepal Journal of Biotechnology, 2020)
Actinomycetes are Gram positive, free living saprophytes which are distributed in soil as one of the major populations and are primary source of antibiotics. This study was carried out with a quest to isolate actinomycetes from soil samples of different places and assess their antibacterial activity. Isolation of actinomycetes was carried out by serial dilution of soil sample followed by spread plate method. The antimicrobial extract was extracted using ethyl acetate. Assessment of antimicrobial activity was performed by using Agar cup plate assay against test organisms (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Salmonella paratyphi, Bacillus subtilis, Staphylococcus aureus). Antibacterial activity was tested against Methicillin Sensitive Staphylococcus aureus and Methicillin Resistant Staphylococcus aureus in the isolates having effective inhibitory activity against Staphylococcus aureus. From 15 soil samples of 12 different locations, 121 actinomycetes isolates were isolated. Among them, 58 (47.9%) isolates were inhibitory against at least 1 test organism in primary screening, of which 22 isolates effective against more than 1 test organism was chosen for secondary screening. Out of them, 8 were inhibitory against 2 test organisms while 14 were inhibitory against 3 test organisms. Staphylococcus aureus was found to be the most susceptible test organism with its susceptibility against 12 actinomycetes isolates. Among 12 isolates effective against Staphylococcus aureus, 10 were found to have an inhibitory effect against Methicillin Susceptible Staphylococcus aureus while 6 were found to have inhibitory effect against Methicillin Resistant Staphylococcus aureus strain. The findings of this study highlight the inhibitory potential of actinomycetes and the need for further investigation for obtaining novel antimicrobial agents from actinomycetes from various unexplored areas.